The Regime of Truth, Partnerships, and Palm Oil Expansion in East Kalimantan, Indonesia - Sudirman Sudirman (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
A large part of the uplands in East Kalimantan has been converted to oil palm plantations through partnership schemes, making it increasingly difficult for the indigenous Dayak people to find land for swidden agriculture. Therefore, a better understanding of partnership discourses and narratives is needed. This article adopts a Foucauldian perspective on truth regimes and ethnographic methods to examine the Indonesian government's strategy to expand state space for oil palm expansion in Dayak customary lands in East Kalimantan. This article argues government strategies need to be formulated by involving a robust analysis of the circular power-knowledge relationship. This perspective allows an understanding of partnerships at the discourse level, i.e., as an extension of power, not just stories about community empowerment behind the invisible hands of capitalism. Oil palm partnerships are a temporary policy structure as it confronts another power‐knowledge configuration: the Dayak community. Within this framework, customary practices are not static but are redefined continuously. In the uplands of East Kalimantan, oil palm agribusiness partnership policies often result in subjugating, disqualifying, and marginalizing practices. This article also investigates the implications of the formation of oil palm truth regimes.